Institutional vulnerability and trust in public agencies: Views from both sides of the street. Issue 4 (16th July 2021) - Spink, Peter; Lotta, Gabriela; Burgos, Fernando
Abstract: This article seeks to contribute to the discussion of the dynamics of trust in street‐level public sector work, especially in settings where relationships between agencies, frontline workers, and society are fragile. Data was gathered in different vulnerable areas of the city of São Paulo, Brazil using interviews with frontline workers and complemented with field notes from a five‐year longitudinal study in one high‐density area with a history of violence. Concern was to understand how, despite a lack of reciprocal trust, citizens and service providers create ways of meeting daily demands and how, in doing so, they see each other. Results show that in vulnerable settings, issues of inter‐agency cooperation and territorial connectivity between different public sector services can be more important than individual agency performance in helping citizens find solutions to the problems they are facing. In the absence of an effective inter‐institutional framework, trust is quickly eroded.